Case Report: Prenatal diagnosis of gastrointestinal defects and immunodeficiency syndrome caused by compound heterozygous mutations in TTC7A gene - Han, Shuning; Wang, Miaomiao; Jin, Pengzhen; Hong, Jiawei; Xu, Chunfei; Dong, Minyue (Frontiers in Immunology, 2025)
Gastrointestinal defects and immunodeficiency syndrome (GIDID) is a rare and complex disorder characterized by concurrent dysfunction of the digestive and immune systems. Typically manifesting in infancy or early childhood, GIDID carries a severe prognosis with high early mortality rates. The syndrome has been specifically linked to mutations in the TTC7A gene located on chromosome 2p21. Although GIDID can present during the fetal period, reports of prenatal diagnosis remain exceptionally rare. In this study, we investigated a case involving a fetus with gastrointestinal abnormalities detected during prenatal screening, conceived by a consanguineous couple. Following termination of the pregnancy, whole-exome sequencing of the affected fetus revealed compound heterozygous variants (c.2378del and c.2357G>T) in the TTC7A gene (OMIM:609332). These findings provide critical insights for the prenatal diagnosis of GIDID and enhance fetal detection rate. Furthermore, this study expands the spectrum of known pathogenic mutations in the TTC7A gene and underscores the significant utility of fetal whole-exome sequencing for diagnosing this condition.